Two electron interference in angular resolved double photoionization of Mg - Sokell, E.; Bolognesi, P.; Kheifets, A.; Bray, Igor; Safgren, S.; Avaldi, L. (Institute of Physics Publishing, 2014)
The signature of the target wavefunction has been observed in the symmetrized amplitude of the resonant double photoionization of Mg. This observation is based on our experimental study of angle-resolved double photoionization of Mg at the photon energy of 55.49 eV (2p → 3d resonance) under equal energy sharing conditions.